Is there any association between osteoporotic vertebral fracture and vitamin K epoxide reductase complex subunit-1 polymorphism in Turkish society? A pilot study - Merih Ozgen; Didem Turgut Cosan; Fulya Doganer; Ahu Soyocak; Onur Armagan; Selen Kuzgun; Ayse Merve Aydogan; Hasan Veysi Gunes; Irfan Degirmenci; Fezan Mutlu (Clinics, 2019)
OBJECTIVE: In this study, the relationship between osteoporotic vertebral fractures and 9041 Guanine/Adenine and 3673 Guanine/Adenine polymorphisms related to the vitamin K epoxide reductase complex subunit-1 (VKORC1) gene in postmenopausal women with osteoporosis was investigated. METHOD: DNA was isolated from blood samples collected from 150 women with postmenopausal osteoporosis. Genotyping of the two polymorphic regions (9041 Guanine/Adenine and 3673 Guanine/Adenine) in VKORC1 was performed using polymerase chain reaction–restriction fragment length polymorphism analysis. The presence of radiographic fractures among the 150 patients was ascertained by using the Genant method. RESULT: At least one fracture was detected in 98 patients, and no fracture was observed in 52 patients on radiological images. We found no association between the 9041 Guanine/Adenine (p=0.283) and 3673 Guanine/Adenine (p=0.232) polymorphisms of the VKORC1 gene and the development of secondary postosteoporotic fractures in our study. CONCLUSION: There was no relationship between osteoporotic vertebral fracture and VKORC1 gene polymorphism in a postmenopausal Turkish population.